Study Analysis of Voltage Drop in a Typical Office Building Lighting System: A Case Study of of FEM IPB Building Electrical Installation - Chico Hermanu Brillianto Apribowo; Ghea Faradiba; Feri Adriyanto; Oktavian Listiyanto (Universitas Sebelas Maret (UNS), 2019)
Design of electrical system in the Faculty of Economics and Management Bogor Agricultural Institute was based guidance consisting of PUIL, SNI, as well as provisions of modern security and technology and aesthetic beauty. Design is also based on the relevant IEC standards, specifically IEC 60364. In the electrical system, it is necessary to pay attention to the conductor and safety factor to minimize power losses and drop voltage. Losses on the customer side due to drop voltage besides damaging electrical equipment is customers only can have a voltage less than 220 V. The distance between load panel and main panel is directly proportional to the drop voltage value, much farther the load panel to the main panel, resulting greater drop voltage value produced. The calculation of drop voltage based on total load, length, and area of conductor. To overcome the problems that occurred in this case study, the conductor uses 1.25 times the nominal current as a safety factor. The selection area of conductor can be said to be quite good with the farthest drop voltage value from SDP-TR is 0.89%. The total amount of electricity in the building is 158.33 kVA, assuming that if there is an additional 5-10 years, the total electric power and 15% of the others SDP is 182.04 kVA.